THE IMPACT OF TERRORISM ON REAL ESTATE VALUES: THE DIYARBAKIR PROVINCE, SUR DISTRICT EXAMPLE (Third Sector Social Economic Review, 2018)
Anatolia, which has hosted many civilizations, is among the oldest known cultural capitals. The Diyarbakır Fortress and Hevsel Gardens Cultural Landscape, one of the most important historical assets of Turkey, which encompasses the Anatolia and Thrace Peninsulas as well as the northern part of the Mesopotamia within its boundaries, is in the World Cultural Heritage List. The states established in Anatolia and its immediate vicinity have had to deal with terrorist events throughout the history. The history has continued to repeat itself since the establishment of the Republic of Turkey. In this study, after providing general information about the effects of terrorism on real estate values, the Diyarbakır Province, Sur District was examined as an example. This study is important in terms of being the first study on this subject in Turkey. In the study, various printed and electronic resources on terrorism and real estate were reviewed and a survey was conducted covering the immovable sales data obtained from the TKGM (General Directorate of Land Registry and Cadastre) through legal means as well as the people living in the region and offices, bureaus, companies operating in the real estate market, and neighborhood mukhtars (headmen). In the light of the resources searched and the data obtained, an attempt has been made to reveal the effects of terrorism on the real estate market. It has been determined that terror and real estate are as old as human history and there is an inversely proportional relationship between terrorism and real estate values. In the section following the literature analysis, the data belonging to the Sur district of Diyarbakır Province have been analyzed and it has been determined that the effect of terrorism on real estate circulation and its value is 98 percent. It has been concluded that with the positive steps taken by the government such as the solution process and the reconciliation initiative, the real estate market showed a tendency to revive, the ditch (hendek) operations negatively affected the real estate sector and the people of the region are 68% satisfied with the urban renewal works to be conducted. It should be emphasized based on the results of the study that terror has a direct negative impact on real estate values, the Diyarbakır Province, Sur District needs to be cleaned from the elements of terrorism, and it is necessary to provide economic prosperity to the people with the projects that will increase the income levels of the people, in line with the opinions of the people of  the region.
Keywords: Terror; Real Estate; Sur District; Real Estate Markets and Local Economic Development Relations